2015
DOI: 10.1038/srep08505
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced endothelial cell-derived extracellular vesicles modulate the cellular status of pericytes

Abstract: Emerging lines of evidence have shown that extracellular vesicles (EVs) mediate cell-to-cell communication by exporting encapsulated materials, such as microRNAs (miRNAs), to target cells. Endothelial cell-derived EVs (E-EVs) are upregulated in circulating blood in different pathological conditions; however, the characteristics and the role of these E-EVs are not yet well understood. In vitro studies were conducted to determine the role of inflammation-induced E-EVs in the cell-to-cell communication between va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
134
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 65 publications
3
134
0
Order By: Relevance
“…A number of studies have demonstrated that RNA, DNA, and proteins are encapsulated in EVs as bioactive molecules (Table I) (Al-Nedawi et al, 2009;Cai et al, 2013;Waldenstrom et al, 2012;Yamamoto et al, 2015). Some reports have suggested that the bioactive molecules encapsulated in EVs play important roles in intercellular communication, and in specific signal transductions in the pathophysiological states of cells both in vitro and in vivo (Kawamoto et al, 2012;Tominaga et al, 2015;Yamamoto et al, 2015).…”
Section: Bioactive Molecules Encapsulated In Evsmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have demonstrated that RNA, DNA, and proteins are encapsulated in EVs as bioactive molecules (Table I) (Al-Nedawi et al, 2009;Cai et al, 2013;Waldenstrom et al, 2012;Yamamoto et al, 2015). Some reports have suggested that the bioactive molecules encapsulated in EVs play important roles in intercellular communication, and in specific signal transductions in the pathophysiological states of cells both in vitro and in vivo (Kawamoto et al, 2012;Tominaga et al, 2015;Yamamoto et al, 2015).…”
Section: Bioactive Molecules Encapsulated In Evsmentioning
confidence: 99%
“…Some reports have suggested that the bioactive molecules encapsulated in EVs play important roles in intercellular communication, and in specific signal transductions in the pathophysiological states of cells both in vitro and in vivo (Kawamoto et al, 2012;Tominaga et al, 2015;Yamamoto et al, 2015).…”
Section: Bioactive Molecules Encapsulated In Evsmentioning
confidence: 99%
See 3 more Smart Citations